2014
DOI: 10.1177/0269881114550355
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cannabidiol in the treatment of patients with Parkinson’s disease: An exploratory double-blind trial

Abstract: Our findings point to a possible effect of CBD in improving quality of life measures in PD patients with no psychiatric comorbidities; however, studies with larger samples and specific objectives are required before definitive conclusions can be drawn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
227
1
23

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 295 publications
(252 citation statements)
references
References 24 publications
1
227
1
23
Order By: Relevance
“…The study by Carrol et al [17] was the only one considered class I for the purposes of evidence-based recommendations. Various doses of cannabidiol were given to 21 patients over 6 weeks; no change was found in the total motor score, despite improvement in the quality of life section of the Unified Parkinson's disease rating scale if the target dose of 300 mg daily was reached, which was possible in only 35 % of the patients [18]. Finally, an open-Blabel^study of smoked marijuana in 22 Israeli patients showed improvement in the number of dyskinesias observed after dopa challenge, 30 min after smoking the cigarette [19].…”
Section: Dyskinesias From Levodopa (In Advanced Pd)mentioning
confidence: 99%
“…The study by Carrol et al [17] was the only one considered class I for the purposes of evidence-based recommendations. Various doses of cannabidiol were given to 21 patients over 6 weeks; no change was found in the total motor score, despite improvement in the quality of life section of the Unified Parkinson's disease rating scale if the target dose of 300 mg daily was reached, which was possible in only 35 % of the patients [18]. Finally, an open-Blabel^study of smoked marijuana in 22 Israeli patients showed improvement in the number of dyskinesias observed after dopa challenge, 30 min after smoking the cigarette [19].…”
Section: Dyskinesias From Levodopa (In Advanced Pd)mentioning
confidence: 99%
“…It acts via various mechanisms, such as inhibition of primary afferent nerve activity, decrease in neuronal response to a noxious stimulus, and inhibition of mast cell degranulation (Richardson, 2000). The effect of cannabinoid-related drugs on PD symptoms is still controversial (Sieradzan et al, 2001;Carroll et al, 2004;Venderov a et al, 2004;Chagas et al, 2014). A study from our Movement Disorders Clinic showed that treatment with medical cannabis was associated with a decrease in motor and pain scores as well as an improvement in sleep quality (Lotan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…60 A sintomatologia da DP inclui tremores involuntários, braquidinesia, instabilidade postural e rigidez, evoluindo para incontinência, incapacidade funcional e morte. 61 A fisiopatologia da doença está relacionada à degeneração de neurônios dopaminérgicos, 62 possivelmente devido ao estresse oxidativo e à um complexo processo neuroinflamatório, especialmente na substância negra do cérebro.…”
Section: Doença De Parkinson (Dp)unclassified